2012
DOI: 10.4141/cjps2011-197
|View full text |Cite
|
Sign up to set email alerts
|

Viruses as triggers of DNA rearrangements in host plants

Abstract: Andronic, L. 2012. Viruses as triggers of DNA rearrangements in host plants. Can. J. Plant Sci. 92: 1083–1091. Assessment of microsporogenesis in tomato (Lycopersicon esculentum, cultivars Fachel, Nistru and Prizior) infected with tomato aspermy virus or potato virus X and barley (Hordeum vulgare L., cultivars Galactic, Sonor, Unirea) infected with barley stripe mosaic virus showed deviations in the conjugation of homologous chromosomes and segregation of genetic material, expressed in the disruption of chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Previous work has demonstrated that pathogens increase recombination in plants during meiotic and somatic (non-gamete) division [7][8][9] . That the few existing examples of this phenomenon span plants and animals suggests that pathogen-induced increases in the recombinant fraction could be widespread, although perhaps achieved through different means, for example transmission distortion in flies but higher recombination in plants.…”
Section: R O M E E L Dav émentioning
confidence: 99%
“…Previous work has demonstrated that pathogens increase recombination in plants during meiotic and somatic (non-gamete) division [7][8][9] . That the few existing examples of this phenomenon span plants and animals suggests that pathogen-induced increases in the recombinant fraction could be widespread, although perhaps achieved through different means, for example transmission distortion in flies but higher recombination in plants.…”
Section: R O M E E L Dav émentioning
confidence: 99%
“…Theoretical models indicate that increased genetic mixing via recombination can allow organisms to more rapidly evolve to shifting parasitic pressures in their environment, a consideration that may pose a major evolutionary advantage to sex and recombination [ 48 50 ]. Indeed, sex and meiotic recombination have been shown to evolve [ 51 53 ] and plastically increase [ 54 56 ] in response to pathogen pressures in species with facultative sexual reproduction. However, evidence that pathogen pressures can trigger increases in meiotic recombination rates in host species with obligate sexual reproduction is currently limited to Drosophila [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…). Similarly, exposure to parasites has been associated with elevated recombination rates (Andronic ; Singh et al. ), and nutrient stress is associated with increased recombination rates in yeast (Abdullah and Borts ) and Drosophila (Neel ).…”
mentioning
confidence: 99%
“…For instance, social stress has been associated with increased recombination rates in mice (Belyaev and Borodin 1982), and temperature is known to affect rates of crossing-over in Drosophila (Plough 1917(Plough , 1921Stern 1926;Smith 1936;Grushko et al 1991). Similarly, exposure to parasites has been associated with elevated recombination rates (Andronic 2012;Singh et al 2015), and nutrient stress is associated with increased recombination rates in yeast (Abdullah and Borts 2001) and Drosophila (Neel 1941). Further, a clear link between maternal age and recombination rate has been found in humans (e.g., Kong et al 2004;Hussin et al 2011), mice (Henderson andEdwards 1968;Luthardt et al 1973) and Drosophila (Stern 1926;Bridges 1927;Redfield 1964;Lake 1984;Chadov et al 2000;Priest et al 2007;Tedman-Aucoin and Agrawal 2012;Hunter et al 2016b).…”
mentioning
confidence: 99%